Contribution to the Analysis of the Interface Strategy- Quality Approach of Moroccan Companies Certified ISO 9001: The Mediating Role of Performance (Global Journal of Management and Business Research, 2018)
Abstract not found
Keywords: quality approach; business strategy; relationship; model; quality behavior; QMS; competitive advantage